Safety and efficacy of tyrosine kinase inhibitors for the treatment of multiple sclerosis: A systematic review and meta-analysis from randomized controlled trials - Yan, Zeya; Gu, Feng; Wang, Zilan; Meng, Jiahao; Tao, Xinyu; Dai, Qiling; Wang, Wei; Liu, Meirong; Wang, Zhong (Frontiers in Neurology, 2022)
Background Multiple sclerosis (MS), an autoimmune disease, is characterized by inflammatory demyelinating lesions in the white matter of the central nervous system. Drugs targeting tyrosine kinase, a critical component of immune cell receptor signaling, have been developed to treat MS. However, the exact efficacy and safety of tyrosine kinase inhibitors (TKIs) are still controversial, and comprehensive analysis with a high level of evidence is needed. Methods Medline, Embase, Cochrane Library, and Clinicaltrials.gov for randomized controlled trials (RCTs) evaluating TKIs versus placebo for MS were searched up to April 1st, 2022. The risk ratio (RR) and mean difference (MD) or standard mean difference (SMD) were analyzed using dichotomous outcomes and continuous outcomes, respectively, with a random effect model. Results A total of 1,043 patients derived from four clinical trials were included to investigate the efficacy and safety of TKI therapy for MS. According to our analysis, TKIs decreased the cumulative number of gadolinium-enhancing lesions on T1-weighted MRI with the application of high dose (SMD = −0.61, 95% CI: −0.93 to −0.30, P = 0.0001). Meanwhile, TKIs prevented the expanded disability status scale (EDSS) from rising (MD = −0.10, 95% CI: −0.19 to −0.00, P = 0.046). In terms of MS relapse, TKIs have not revealed an obvious statistical difference compared with placebo (RR = 0.96, 95% CI: 0.55–1.65, P = 0.8755). However, more adverse events seem to occur in the TKIs group, both for adverse events (RR = 1.12, 95% CI: 1.05–1.19, P = 0.0009) and serious adverse events (RR = 1.91, 95% CI: 1.30–2.81, P = 0.001). Conclusion Tyrosine kinase inhibitors have shown promise in treating MS. Generally, TKIs that attain the effective dose demonstrate definite efficacy and have tolerable side effects. More clinical trials and validation are needed, and we anticipate that TKIs will be a viable alternative for MS patients.